In the Process of Self-development - Shikha Verma (International Journal on Integrated Education, 2021)
The main objective of this study is to identify how much the professionals are willing for their self-development. The researcher has conducted an online survey. This online test was an objective assessment test. The purpose is also to motivate the professionals to think over their strength and weaknesses. Thereafter, to identify the areas of their interests. The paper will support the reader to plan for their self-development. The researcher has also suggested to draw an outline for the continuous professional development (CPD).